Gatotkaca Costume Analysis in Satria Dewa Movie and It's Impact to Gatotkaca's Character Brand Image - Tirtadarma, Edo (Universitas Multimedia Nusantara, 2023)
Indonesia has many folklores that passed down generation to generation. One of the famous folklore is the epic tale of Mahabharata. The story is about the long last war between good and evil. The god side represented by Pandawa, and the bad side represented by Kurawa. This Mahabharata epic tale, has one character that take interest as one of the main character, the name is Gatotkaca. The story of Gatotkaca was turn into live action movie by Satria Dewa Studio. This movie reshapes the image of traditional Gatokaca into a new one started by redesigned Gatotkaca. Changing the looks with a new costume creates a new impact and perspective especially the brand image about Gatot Kaca in this movie. This paper analyses Gatotkaca new costume in the movie. The methodology approach is qualitative method with descriptive literature study approach. The result of this research is Gatotkaca new costume is changing the image, and gives new meaning in term of representation about character, make the Mahabarata epic story for suitable for young generation as they become the new targeted audience of the movie. Keywords: brand; image; costume; movie.